Serum HBV pregenomic RNA is correlated with Th1/Th2 immunity in treatment‐naïve chronic hepatitis B patients. Issue 3 (21st November 2019) - Gu, Yurong; Chen, Lubiao; Lian, Yifan; Gu, Lin; Chen, Yaqiong; Bi, Yanhua; Huang, Zexuan; Huang, Yanlin; Hu, Bo; Huang, Yuehua
Abstract: Background and Aim: Hepatitis B virus (HBV) load and antigens are related to the innate and adaptive immunity of chronic hepatitis B (CHB) patients. As a new HBV biomarker, the role of pregenomic RNA (pgRNA) in host immunity is not known. This study aimed to identify the relationship between serum HBV pgRNA and host immunity in CHB patients. Methods: Two hundred twenty‐five treatment‐naïve CHB patients were enrolled. Serum cytokines were measured by cytokine antibody array (Luminex multiplex platform). Th1 (T‐helper cell, Th) and Th2 cells were tested by flow cytometry. Serum HBV pgRNA was detected by a reverse transcription‐polymerase chain reaction. Results: Serum HBV pgRNA was significantly different among patients in different disease phases and significantly associated with both HBV antigens and antibodies. Serum HBV pgRNA was positively correlated with the HBsAg level ( P < .001) and the presence of HBeAg ( P < .001). Patients with higher HBcAb levels showed lower serum HBV pgRNA levels ( P = .003). Notably, HBsAb positivity was associated with higher levels of serum HBV pgRNA in HBeAg(−) patients ( P = .049). Serum HBV pgRNA was positively associated with ALT level, Th2 cell frequency, and related cytokine sCD30 ( P < .001, P < .001, and P = .003, respectively), but negatively associated with Th1‐related cytokine interleukin (IL)‐12P70 and cytotoxic lymphocytes (CTLs) ( P = .017 and P < .001, respectively). Conclusion: Our study confirmed the relationship between serum HBV pgRNA and host immunity. The results demonstrated that serum HBV pgRNA is positively correlated with Th2 immunity but negatively correlated with Th1 immunity, indicating that it might have a relationship with HBV antigen conversion and CTL immunodeficiency in CHB patients. Highlights: Serum HBV pgRNA had a relationship with host immunity. Serum HBV pgRNA was positively correlated with Th2 cells and cytokines. Serum HBV pgRNA was negatively correlated with CTLs and Th1 cytokine.